Genomics of selected human odorant receptors - Knape, Kirsten; Beyer, Anton; Stary, Anna; Buchbauer, Gerhard; Wolschann, Peter (Monatshefte für Chemie, 2008)
Single nucleotide polymorphisms (SNPs) in odorant receptor genes may influence the protein sequence and consequently also the function of the receptors. An analysis of the HapMap data for human OR3A1 was performed and provided evidence that genetic differences subject to ancestry and gender can be recognized. A genomic comparison of individuals shows the diversity of odorant receptor genes and therefore potentially the variety of the sense of smell. At this time, two complete human genomes are available in public domain, which we used for this purpose.